A GENESIS OF GENERAL KKM THEOREMS FOR ABSTRACT CONVEX SPACES: REVISITED - Park, S. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2013)
In our previous work [4], we obtained three general KKM type theorems A, B, and C for abstract convex spaces. In this paper, we show that these three theorems are mutually equivalent. Actually, by adopting a method of making new abstract convex spaces from old, we give a direct proof of Theorem C from Theorem B.